ENERGY AND PARTICLE FLOW IN 3-JET AND RADIATIVE 2-JET EVENTS FROM HADRONIC Z-DECAYS - Acciarri, M; Adam, A; Adriani, O; Aguilarbenitez, M; Ahlen, S; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; et al. (1995)
We report on a detailed study of the energy and particle flow in the event plane of three-jet events (qqg) and radiative two-jet events (qqγ) in hadronic Z decays recorded with the L3 detector. We find a significant decrease in particle and energy density in the angular region between quark and antiquark jets for qqg events as compared with qqγ events. Several QCD model predictions are compared with the observed effect. © 1995.